1976
DOI: 10.1002/cpt1976196738
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and circulatory effects of intravenous butorphanol and morphine

Abstract: The respiratory and circulatory effects and other side effect liability 0/ intravenous doses 0/30 and 60 f.Lg/kg butorphanol, 150 to 300 f.Lg/kg norphine, and a placebo were investigated in a crossover double-blind study.Butorphanol (L-N -eyclobutymethyl-3-14ßdihydroxymorphinan) is a synthetie morphinan derivative. Like pentazoeine, it is an agonistantagonist with relatively potent analgesie and weak antagonistie aetivity. In earlier elinieal pharmaeologieal studies its analgesie aetivity by weight was estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The effect of B is certainly no less than that of M at this dose, but other workers have shown that B differs from M when larger doses are given. While respiratory depression is progressively more severe as larger doses of M are used, there seems to be no significant increase between the effects of doses of 30 and 60 J.Lg/kg of BY' 15 Nevertheless, although the effects we report are small they are of a degree which may be clinically important to patients with respiratory impairment.…”
Section: Discussionmentioning
confidence: 60%
“…The effect of B is certainly no less than that of M at this dose, but other workers have shown that B differs from M when larger doses are given. While respiratory depression is progressively more severe as larger doses of M are used, there seems to be no significant increase between the effects of doses of 30 and 60 J.Lg/kg of BY' 15 Nevertheless, although the effects we report are small they are of a degree which may be clinically important to patients with respiratory impairment.…”
Section: Discussionmentioning
confidence: 60%
“…So our results cannot be extrapolated to longer duration intracranial surgeries. Second, we used butorphanol because of the advantages of butorphanol [3,4,[9][10][11][12]19,20] and problems associated during the use of newer opioids analgesics (fentanyl, remifentanil etc.) like need for frequent administration, limited availability, need for infusion system for their delivery, and their cost.…”
Section: Discussionmentioning
confidence: 99%
“…Butorphanol has also been reported to provide adequate analgesia when used as a supplement in balanced anesthetic technique [3] and at doses between 30-60 µg/kg butorphanol is reported to produce no or minimal cardiovascular changes [4]. Unfortunately, studies on exact dose requirement during propofol induction and maintenance anesthesia along with butorphanol with and without the use of N 2 O during craniotomies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the dominant control of ventilation is mediated through an increase in PaCO 2 , which strongly stimulates central chemoreceptors, 119 leading to increased ventilation. RD from morphine is characterized by a dose-related, naloxone-reversible depression of resting minute ventilation (Ve) with proportional reduction of tidal volume (Vt), [120][121][122] decreased PaO 2 and pH, increased PaCO 2 , 121,123 and decreased ventilatory drive stimulated by hypercapnia and hypoxia. 124,125 In volunteers, ITM caused a dose-related depression of medullary respiratory centre sensitivity to ventilatory stimulus.…”
Section: Discussionmentioning
confidence: 99%